2017
DOI: 10.1007/s40272-017-0234-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Stability of Dopamine and Dobutamine Over 24 h in Simulated Neonatal Ward Conditions

Abstract: Objectives. Our objectives were to investigate the possible effects temperature and light have on the stability of dopamine and dobutamine continuous infusions over 24 hours when prepared in varying dilution vehicles.Methods Syringe-driver infusion apparatuses were set up of either dopamine or dobutamine, diluted with either 0.9% sodium chloride or 5% glucose, delivering 3mcg/kg/min and 5mcg/kg/min respectively via 206 cm extension sets. All infusions were prepared for a neonate weight of 1 kg. Infusions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The concentration of dopamine during infusion has seldom been investigated as a cause and this study showcases the observed changes in dopamine concentration during infusion in a laboratory-simulated environment that replicates an infusion administered to a neonate within an incubator in an intensive care unit. To date, only our previous study has shown that in a clinical environment dopamine stability varies,20 and this investigation adds further information covering a range of dilution vehicles and neonatal weights. These findings provide significant insight into the impact of dose variation during infusion changeover when a 24-hour dosing cycle is used.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The concentration of dopamine during infusion has seldom been investigated as a cause and this study showcases the observed changes in dopamine concentration during infusion in a laboratory-simulated environment that replicates an infusion administered to a neonate within an incubator in an intensive care unit. To date, only our previous study has shown that in a clinical environment dopamine stability varies,20 and this investigation adds further information covering a range of dilution vehicles and neonatal weights. These findings provide significant insight into the impact of dose variation during infusion changeover when a 24-hour dosing cycle is used.…”
Section: Discussionmentioning
confidence: 82%
“…Despite great efforts being made to simulate neonatal ward conditions as accurately as possible in a laboratory setting, there are a few experimental design limitations which can affect the interpretation of the data. These are highlighted in our previous publication and include the nature of the incubator used, which does not allow for maximal light, as used on the neonatal ward, therefore underestimating the degree of degradation 20. Another important consideration is that our study is a very simple clinical model that does not fully mimic drug delivery of inotropes, as often they are coadministered with other compounds, formulations or parenteral nutrition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations